2006
DOI: 10.1073/pnas.0608715103
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism for analgesia involving specific antagonism of α9α10 nicotinic acetylcholine receptors

Abstract: ␣9␣10 nicotinic acetylcholine receptors (nAChRs) have been identified in a variety of tissues including lymphocytes and dorsal root ganglia; except in the case of the auditory system, the function of ␣9␣10 nAChRs is not known. Here we show that selective block (rather than stimulation) of ␣9␣10 nAChRs is analgesic in an animal model of nerve injury pain. In addition, blockade of this nAChR subtype reduces the number of choline acetyltransferase-positive cells, macrophages, and lymphocytes at the site of injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
264
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(280 citation statements)
references
References 29 publications
6
264
1
2
Order By: Relevance
“…Early studies suggested that interaction with 3 subunit-containing nAChRs may mediate these actions (Livett et al 2006), but the affinity of Vc1.1 and AuIB for these subtypes is rather weak (Clark et al 2006;Vincler et al 2006). Vc1.1 and RgIA are both potent antagonists of α9α10 nAChRs, suggesting this may be the anti-allodynia target (Vincler et al 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies suggested that interaction with 3 subunit-containing nAChRs may mediate these actions (Livett et al 2006), but the affinity of Vc1.1 and AuIB for these subtypes is rather weak (Clark et al 2006;Vincler et al 2006). Vc1.1 and RgIA are both potent antagonists of α9α10 nAChRs, suggesting this may be the anti-allodynia target (Vincler et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Early studies suggested that interaction with 3 subunit-containing nAChRs may mediate these actions (Livett et al 2006), but the affinity of Vc1.1 and AuIB for these subtypes is rather weak (Clark et al 2006;Vincler et al 2006). Vc1.1 and RgIA are both potent antagonists of α9α10 nAChRs, suggesting this may be the anti-allodynia target (Vincler et al 2006). However, MII and AuIB are both devoid of activity at α9α10 nAChRs (McIntosh et al 1999;Callaghan et al 2008;Azam and McIntosh 2009;Callaghan and Adams 2010;Klimis et al 2011) and other -conotoxin analogues that act on these nAChRs fail to inhibit allodynia (Nevin et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Neuronal nAChRs are a diverse class of ligand-gated ion channels involved in neurological conditions such as neuropathic pain [52,53] and Alzheimer's disease [54,55]. Therefore, a suite of potent and selective ligands would be an invaluable pharmacological tool to identify the physiological role of nAChR subunit combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially more interesting are the neuronally selective α-conotoxins that target nAChR subtypes comprising different combinations of α3-α10 and/or β2-β4 subunits expressed as either homomeric or heteromeric receptors depending on the neuronal cell type. Interestingly, α-conotoxin Vc1.1 (Sandall et al 2003) and RgI (Vincler et al 2006) have been identified as having potential analgesic properties following peripheral administration to rats. This result contrasts with the analgesic effects usually attributed to agonists of the nAChR acting centrally, and appears to be mediated by a specific subtype of the receptor (α9α10) possessing a previously unrecognised role in pain (Vincler et al 2006), although the involvement of this target in its analgesic action has been questioned (Nevin et al 2007).…”
Section: A -Conotoxinsmentioning
confidence: 99%
“…Interestingly, α-conotoxin Vc1.1 (Sandall et al 2003) and RgI (Vincler et al 2006) have been identified as having potential analgesic properties following peripheral administration to rats. This result contrasts with the analgesic effects usually attributed to agonists of the nAChR acting centrally, and appears to be mediated by a specific subtype of the receptor (α9α10) possessing a previously unrecognised role in pain (Vincler et al 2006), although the involvement of this target in its analgesic action has been questioned (Nevin et al 2007). Metabolic Pharmaceuticals Ltd has discontinued clinical trials of Vc1.1 due to an anticipated lack of efficacy in humans when it was revealed experimentally that Vc1.1 had low affinity for the human form of the α9α10 receptor.…”
Section: A -Conotoxinsmentioning
confidence: 99%